Endogenic intoxation in blood under conditions of combination pathology - immobilizational stress and adrenaline myocardial damage and correction of L-arginin - O. B. Lys; M. S. Regeda (Kazimierz Wielki University, 2019)
The syndrome of endogenous intoxication, which accompanies pathological processes, is caused by many mechanisms. Erythrocyte index of intoxication (EII) is one of the markers of endogenous intoxication. Medium Molecules (MSM) are products of catabolis m of endo- and exogenous proteins. The aim. of the study was to investigate the effect of L-arginine on the level of endogenous intoxication that occurs in the blood of white rats under the influence of acute immobilization stress and adrenal damage to the myocardium. Material and methods. The experiments were carried out on white male rats of the Vistar line weighing 180-200 g, which were divided into 3 groups of 10 animals (two experimental and one control). MSM254 MSM280 and EII in blood was determined. Results. The level of MSM254 increased by 1,3 times (p